A new class of 8-hydroxy xanthenone and xanthene1, 8-diols: Reduction of xanthenedione derivatives. Issue 3 (1st February 2022) - Shashi, R.; Begum, Noor Shahina; Foro, Sabine
Abstract: The present work reports a simple, mild and efficient protocol for the reduction of xanthenediones to 8-hydroxy xanthenones and xanthene1, 8-diols by using readily available, cost efficient, easy to handle sodium borohydride as the reducing agent. The products obtained are in good to excellent yields with a short reaction duration. The versatility of the reaction, mild reaction conditions, in combination of high yields and easy work-up makes this reaction noteworthy. The synthesized compounds were analyzed spectroscopically. Further, four derivatives were recrystallized and structures were confirmed by crystallographic studies. The crystal structures are stabilized by intermolecular O–H···O hydrogen bonds and C–H···O weak interactions. Graphical Abstract: UF0001